Who rejects depathologization? Attitudes of Russian-speaking trans people toward revision of the International Classification of Diseases. Issue 1 (2nd January 2017) - Kirey-Sitnikova, Yana
ABSTRACT: Post-Soviet space is underrepresented in international discussions on trans depathologization, and voices of trans people (as distinct from activists and experts) are rarely heard. The article seeks to fill this gap by introducing debates on depathologization among trans activists and nonactivist trans people of post-Soviet countries. In order to take into account opinions of various groups of trans people, a survey was conducted concerning the revision of the International Classification of Diseases and various trans-related policies. Classification models were developed to find relationships between demographic data and answers to the questions about depathologization and legal gender recognition.